Magnetic resonance elastography measured shear stiffness as a biomarker of fibrosis in pediatric nonalcoholic fatty liver disease. Issue 5 (9th October 2017) - Schwimmer, Jeffrey B.; Behling, Cynthia; Angeles, Jorge Eduardo; Paiz, Melissa; Durelle, Janis; Africa, Jonathan; Newton, Kimberly P.; Brunt, Elizabeth M.; Lavine, Joel E.; Abrams, Stephanie H.; Masand, Prakash; Krishnamurthy, Rajesh; et al.
Abstract : Magnetic resonance elastography (MRE) is a promising technique for noninvasive assessment of fibrosis, a major determinant of outcome in nonalcoholic fatty liver disease (NAFLD). However, data in children are limited. The purpose of this study was to determine the accuracy of MRE for the detection of fibrosis and advanced fibrosis in children with NAFLD and to assess agreement between manual and novel automated reading methods. We performed a prospective, multicenter study of two‐dimensional (2D) MRE in children with NAFLD. MR elastograms were analyzed manually at two reading centers, and using a new automated technique. Analysis using each approach was done independently. Correlations were determined between MRE analysis methods and fibrosis stage. Thresholds for classifying the presence of fibrosis and of advanced fibrosis were computed and cross‐validated. In 90 children with a mean age of 13.1 ± 2.4 years, median hepatic stiffness was 2.35 kPa. Stiffness values derived by each reading center were strongly correlated with each other (r = 0.83). All three analyses were significantly correlated with fibrosis stage (center 1, ρ = 0.53; center 2, ρ = 0.55; and automated analysis, ρ = 0.52; P  < 0.001). Overall cross‐validated accuracy for detecting any fibrosis was 72.2% for all methods (95% confidence interval [CI], 61.8%‐81.1%). Overall cross‐validated accuracy for assessing advanced fibrosis was 88.9% (95% CI, 80.5%‐94.5%) for center 1, 90.0% (95% CI, 81.9%‐95.3%) for center 2, and 86.7% (95% CI, 77.9%‐92.9%) for automated analysis. Conclusion : 2D MRE can estimate hepatic stiffness in children with NAFLD. Further refinement and validation of automated analysis techniques will be an important step in standardizing MRE. How to best integrate MRE into clinical protocols for the assessment of NAFLD in children will require prospective evaluation. (Hepatology 2017;66:1474–1485)